INTENSITAS PEMBELAJARAN TEMATIK INTEGRATIF MELALUI PENDEKATAN SAINTIFIK DI SD KESTALAN SURAKARTA - Soewalni Soekirno, Oktiana Handini (Widya Wacana: Jurnal Ilmiah, 2019)
This community service aims (1). Providing a scientific basis for elementary school teachers in implementing learning that is oriented towards active, effective and enjoyable learning. (2). Provide theoretical clarity and a better understanding of learning, learning objects and the situations and conditions of learning in elementary schools. (3). Contribute ideas to education managers in an effort to improve teacher professional competency and learner ability in elementary schools, especially at SD Kestalan Surakarta. Community service is carried out in an effort to deliver competence in terms of Integrative Thematic Learning Intensity through Scientific Approach at Kestalan Elementary School Surakarta as a partner school in the Surakarta Teacher Training and Education Faculty, followed by 26 teachers and Principals with a 6-hour implementation period, starting at 8:00 p.m. until 15:00 p.m. The outcome of this community service is that community service resulted in the delivery of material on the Scientific approach to integrative thematic learning in Primary Schools in an effort to optimize teacher understanding and implementation in primary schools in general and SD Kestalan Surakarta in particular. The expected results from the implementation of this service can provide an understanding of the Intensity of Integrative Thematic Learning through the Scientific Approach in Primary Schools. So Kestalan Surakarta Elementary School teachers have 90 percent of the ability to Integrative Thematic Learning through the Scientific Approach in Primary Schools. So that the teachers can transmit their understanding to fellow teachers in the Dabin and Gugus areas as well as primary school teacher meetings. And finally, the results of this service can be published in the service journal.Â Key words: Integrative Thematic Learning, Scientific Approach